(untitled) (Research, Society and Development, 2024)
Faced with the challenges related to the practice of breastfeeding, many actions and strategies have been implemented, with the aim of promoting protecting and supporting breastfeeding, especially in hospital institutions, through interprofessional and intersectoral practice in care line, based on public health policies. The study aimed to analyze the scientific evidence that points to the actions implemented by the interprofessional team, within the scope of breastfeeding, in hospital institutions. This is an integrative review of the literature, where the search was through the Virtual Health Library (VHL) portal, on the Intranet website of the Universidade Federal Fluminense (UFF), using the bases: Scientific Electronic Library Online (SciELO); International Literature in Health Sciences (MEDLINE), by the National Library of Medicine (Pubmed); Latin American and Caribbean Literature in Health Sciences (LILACS); Elsevier (Scopus) and Web of Science (Clarivate Analytics). Of the 2,940 articles initially selected, eight made up the final sample. In general, the studies highlighted actions and interventions, within the scope of breastfeeding, in hospital institutions. However, a weakness in interprofessional practice was revealed, with the need for greater articulation of the actions developed, which could expand the scope of action and, consequently, contribute to better results, in favor of exclusive breastfeeding and the reduction of early weaning hospital, as recommended by the Ministry of Health.